Student Complain Information System (SIPMA) using the Laravel Framework at Handayani University Makassar - Asriana, Rina; Sadli, Adi; Wahyuni, Eka Dyar (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The objective of this study is to provide an innovative solution to enhance communication between students and university administration by designing a student complaint management system. In this context, the system is designed to facilitate efficient and effective handling of student complaints. Through a web-based application, students can easily submit complaints anytime and anywhere using an internet-connected device. The key features of the developed system include online complaint submission, real-time notifications, complaint status tracking, and a complaint management system that enables university administrators to respond to and resolve issues more promptly. The success indicators of this system include a fast response time—where complaints can be processed quickly—and a high level of user satisfaction regarding the efficiency and ease of use of the system. In this study, we adopted the Waterfall development methodology due to its structured and systematic approach, which facilitates planning and testing at each stage of development. This method allows developers to focus on one phase at a time, reducing the risk of errors during implementation. Furthermore, the Laravel framework was chosen for its ease of management, Model-View-Controller (MVC) architecture—which separates application logic from the user interface—and robust security features to protect user data and system integrity. The results of this study demonstrate that a student complaint system can be successfully designed and implemented, offering an effective solution for complaint management in educational settings. With this system, communication between students and university staff is expected to improve, and issues can be resolved more efficiently.